Utilizing Blended Learning to Mitigate the Challenges Brought by Natural Disasters in South African Schools - Ramulumo, Moleboheng; Mohapi, Soane (Research in Social Sciences and Technology- OpenED Network, 2023)
This study investigated the potential benefits and challenges associated with the implementation of blended learning as a strategy for curriculum recovery and enhancement of student performance in Grade 12 science and mathematics education. Blended learning, which combines traditional face-to-face teaching methods with online learning, was recognized for its capacity to address educational difficulties. The research employed a theoretical framework integrating the Technology Acceptance Model and Sociocultural Constructivism theory to examine the viewpoints of teachers regarding technology adoption and the impact of personal and social interactions on learning outcomes. A qualitative interpretive case study design was employed, and interviews were carried out with four science and mathematics teachers. The findings revealed that teachers acknowledged the advantages of blended learning, including its potential to overcome barriers to learning and augment student engagement. However, external challenges about technology infrastructure, limitations of online platforms, and the necessity for professional development were identified. Teachers displayed varying levels of internal challenges, including familiarity and confidence in implementing blended learning. The study underscored the importance of continuous support, infrastructure development, and pedagogical training to effectively integrate blended learning into science and mathematics classrooms. Therefore, by addressing these challenges and capitalizing on the benefits of blended learning, the potential for improving curriculum recovery and enhancing student performance in the face of disruptions caused by natural disasters and other educational obstacles was emphasized.